The balanced scorecard and EFQM working together in a performance management framework in construction industry - Vukomanovic, Mladen; Radujkovic, Mladen (Journal of Civil Engineering and Management, 2013)
In the recent years the Balanced Scorecard (BSC) and EFQM Excellence Model (EFQM) became very popular performance management (PMM) models. However, many studies showed their flaws, especially in communicating, integrating and aligning Key Performance Indicators (KPI) with strategy, setting targets and conducting benchmarking. BSC or EFQM have always been used alone and regarded as exclusive PMM tools. In contrast, this study introduces a novel PMM framework that relies on the strengths of both BSC and EFQM. The framework uses the Analytic Hierarchy Process (AHP) to connect these two models. At first, AHP is used for setting priorities among competitive strategic objectives and afterwards for selecting KPIs against SMARTER (Specific, Measurable, Achievable, Relevant, Time-bound, Encouraging and Rewarding) criteria. By verifying the framework on the construction industry we discovered that companies can integrate EFQM and BSC to conduct benchmarking, identify best practice, align strategy with the competitive surroundings and selecting strategy aligned KPIs. Using this framework, construction companies can thus achieve strategic control that otherwise by just using BSC could not be achieved. These findings are important because they bring a new perspective on managing organizations and confront many authors who have put EFQM and BSC against each other.